Arthroscopic Soft Tissue Stabilization With Selective Augmentations for Traumatic Anterior Shoulder Instability in Competitive Collision Athletes. Issue 6 (May 2021) - Hoshika, Shota; Sugaya, Hiroyuki; Takahashi, Norimasa; Matsuki, Keisuke; Tokai, Morihito; Morioka, Takeshi; Ueda, Yusuke; Hamada, Hiroshige; Takeuchi, Yasutaka
Background: Many surgeons prefer bony stabilization including Bristow or Latarjet procedures for shoulder instability in collision athletes, even though several potential complications have been reported. There has been a limited number of studies on the midterm outcomes of arthroscopic soft tissue stabilization for anterior shoulder instability in competitive collision athletes. Purpose: To assess the outcomes of arthroscopic soft tissue stabilization in combination with selective augmentation procedures for collision athletes with traumatic anterior shoulder instability Study Design: Case series; Level of evidence, 4. Methods: We retrospectively assessed rugby or American football players (<40 years old) who underwent arthroscopic Bankart or bony Bankart repair with selective augmentations (rotator interval closure and/or Hill-Sachs remplissage) for traumatic anterior shoulder instability between January 2012 and March 2017. Shoulders that required other bony procedures were excluded. Recurrence, complications, return to sport, and functional scores (Rowe score and Subjective Shoulder Value sports score) were investigated. Results: This study included 113 shoulders in 100 patients with a mean age of 20 years (range, 15-36 years) at surgery. Rotator interval closure was performed on 36 shoulders in addition to Bankart repair, and rotator interval closure and Hill-Sachs remplissage were performed on 77 shoulders. The mean follow-up period was 44 months (range, 24-72 months). Of the 113 shoulders, 4 (3.5%) experienced postoperative dislocation, but there were no complications. A total of 93 athletes (93%) attained complete or near complete preinjury sports activity levels. The mean Rowe score significantly improved from 36 (range, 10-75) at presurgery to 96 (range, 35-100; P = .003) at postsurgery. The mean Subjective Shoulder Value sports score significantly improved after surgery, from a mean preoperative score of 22 (range, 0-50) to a postoperative score of 92 (range, 64-100; P = .002). Conclusion: Our treatment strategy, where arthroscopic soft tissue stabilization was combined with selected augmentations, provided good clinical outcomes for competitive collision athletes in terms of low rates of recurrence and complication, a high rate of return to sports, and good shoulder function.